Virus versus host: influenza A virus circumvents the immune responses - Su, Guanming; Chen, Yiqun; Li, Xiaowen; Shao, Jian-Wei (Frontiers in Microbiology, 2024)
Influenza A virus (IAV) is a highly contagious pathogen causing dreadful losses to humans and animals around the globe. As is known, immune escape is a strategy that benefits the proliferation of IAVs by antagonizing, blocking, and suppressing immune surveillance. The HA protein binds to the sialic acid (SA) receptor to enter the cytoplasm and initiate viral infection. The conserved components of the viral genome produced during replication, known as the pathogen-associated molecular patterns (PAMPs), are thought to be critical factors for the activation of effective innate immunity by triggering dependent signaling pathways after recognition by pattern recognition receptors (PRRs), followed by a cascade of adaptive immunity. Viral infection-induced immune responses establish an antiviral state in the host to effectively inhibit virus replication and enhance viral clearance. However, IAV has evolved multiple mechanisms that allow it to synthesize and transport viral components by "playing games" with the host. At its heart, this review will describe how host and viral factors interact to facilitate the viral evasion of host immune responses.